Local interventions for actinic keratosis in organ transplant recipients: a systematic review. (1st January 2019) - Heppt, M.V.; Steeb, T.; Niesert, A.C.; Zacher, M.; Leiter, U.; Garbe, C.; Berking, C.
Summary: Background: Actinic keratosis (AK) in organ transplant recipients (OTRs) has a high risk of progressing to invasive squamous cell carcinoma of the skin. Thus, early and consequent treatment of AKs is warranted in OTRs. Objectives: To summarize the current evidence for nonsystemic treatments of AKs in OTRs. Methods: We performed a systematic literature search in MEDLINE, Embase and the Cochrane Central Register of Controlled Trials (CENTRAL) and hand‐searched pertinent trial registers up to 22 August 2018. Randomized controlled trials (RCTs) evaluating nonsystemic interventions for AKs in OTRs were included. The risk of bias was estimated using the Cochrane Risk of Bias Tool. Results: Of 663 records initially identified, eight RCTs with 242 OTRs were included in a qualitative synthesis. Most studies evaluated methyl aminolaevulinate photodynamic therapy (MAL‐PDT), followed by ablative fractional laser (AFXL) and diclofenac sodium 3% in hyaluronic acid, imiquimod 5% cream and 5‐fluorouracil 5% cream (5‐FU). MAL‐PDT showed the highest rates of participant complete clearance (40–76·4%), followed by imiquimod (27·5–62·1%), diclofenac (41%) and 5‐FU (11%). Similar results were observed for lesion‐specific clearance rates. Treatment with AFXL alone revealed low lesion clearance (5–31%). Local skin reactions were most intense in participants treated with a combination of AFXL and daylight MAL‐PDT. There were no therapy‐related transplant rejections or worsening of graft function in any trial. The overall risk of bias was high. Conclusions: Limited evidence is available for the treatment of AKs in OTRs. MAL‐PDT is currently the best‐studied intervention. Lesion‐specific regimens may not be sufficient to achieve disease control. Field‐directed regimens are preferable in this high‐risk population.